Semi-active suspension system for handling quality and longitudinal stability improvements using hybrid stability augmentation system-force control algorithm - Pakharuddin Mohd. Samin, 1962-, author; Hishamuddin Jamaluddin, author; Roslan Abd. Rahman, author; Saiful Anuar Abu Bakar, supervisor, author; Khisbullah Hudha, author; Regional Conference on Vehicle Engineering and Technology (2nd : 2008 : Hotel Istana, Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL